Current state of speed-strength training for male wushu sanshou athletes aged 14-15 at hanoi training and competition center (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Current state of speed-strength training for male wushu sanshou athletes aged 14-15 at hanoi training and competition center